Evolution of codon usage patterns: the extent and nature of divergence between Candida albicans and Saccharomyces cerevisiae. - Lloyd, A T (1992)
Codon usage in a sample of 28 genes from the pathogenic yeast Candida albicans has been analysed using multivariate statistical analysis. A major trend among genes, correlated with gene expression level, was identified. We have focussed on the extent and nature of divergence between C.albicans and the closely related yeast Saccharomyces cerevisiae. It was recently suggested that significant differences exist between the subsets of preferred codons in these two species [Brown et al. (1991) Nucleic Acids Res. 19, 4293]. Overall, the genes of C.albicans are more A + T-rich, reflecting the lower genomic G + C content of that species, and presumably resulting from a different pattern of mutational bias. However, in both species highly expressed genes preferentially use the same subset of 'optimal' codons. A suggestion that the low frequency of NCG codons in both yeast species results from selection against the presence of codons that are potentially highly mutable is discounted. Codon usage in C.albicans, as in other unicellular species, can be interpreted as the result of a balance between the processes of mutational bias and translational selection. Codon usage in two related Candida species, C.maltosa and C.tropicalis, is briefly discussed.